2002
DOI: 10.1042/cs1020587
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between asymptomatic hypercholanaemia of pregnancy and progesterone metabolism

Abstract: The aim of this study was to identify a subgroup of pregnant women with asymptomatic hypercholanaemia of pregnancy (AHP), in which the relationship between alterations in the level and pattern of serum bile acids (BAs) and of progesterone plus progesterone metabolites could be investigated in the absence of overt impairment of hepatobiliary function. Cholanaemia and serum concentrations of progesterone were assayed by an enzymic technique and by ELISA respectively, while BA molecular species and progesterone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 22 publications
5
29
0
2
Order By: Relevance
“…Furthermore, the mechanism of P4-S-mediated inhibition of bile acid uptake appeared to be mainly competitive in nature in PHH, and this was confirmed in the NTCP-expressing oocytes. These findings are of likely physiological relevance as P4-S rises in normal pregnancy (19), and our data are consistent with these metabolites contributing to the asymptomatic hypercholanemia that is observed in some pregnant women with otherwise normal biochemical liver tests (1,2). Serum levels of P4-S rise further in pregnancies complicated by ICP (21,22) and therefore they may play a role in the hypercholanemia that is reported in this condition.…”
Section: Table 1 Impact Of Pm5-s On Nasupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the mechanism of P4-S-mediated inhibition of bile acid uptake appeared to be mainly competitive in nature in PHH, and this was confirmed in the NTCP-expressing oocytes. These findings are of likely physiological relevance as P4-S rises in normal pregnancy (19), and our data are consistent with these metabolites contributing to the asymptomatic hypercholanemia that is observed in some pregnant women with otherwise normal biochemical liver tests (1,2). Serum levels of P4-S rise further in pregnancies complicated by ICP (21,22) and therefore they may play a role in the hypercholanemia that is reported in this condition.…”
Section: Table 1 Impact Of Pm5-s On Nasupporting
confidence: 76%
“…Normal pregnancy is characterized by altered bile acid homeostasis, and two recent studies have reported asymptomatic hypercholanemia of pregnancy in 10 -40% of pregnant women (1,2). Approximately 25% of women with asymptomatic hypercholanemia of pregnancy subsequently develop intrahepatic cholestasis of pregnancy (ICP), 4 a liver disorder that presents with pruritus, raised serum bile acids, and liver transaminases (3).…”
mentioning
confidence: 99%
“…The present study provides information regarding the mechanisms of cholestasis induced by these compounds, in particular some of the PMs that are elevated in the serum of women with AHP [12] or ICP [4,6]. The present study suggests that inhibition of BA secretion into bile, mainly mediated by BSEP [25], may play an important role in the cholestatic effect induced by metabolites of both estrogens and progesterone.…”
Section: Discussionmentioning
confidence: 72%
“…It is noteworthy that serum concentrations of these PMs are in the micromolar range in healthy pregnant women, are elevated in women with ICP [4] or AHP [12], and are probably further concentrated in bile. Indeed, one of these compounds (PM4-S), when administered to isolated perfused rat livers, was several-fold concentrated in bile (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation